Quercetin Enhances Inhibitory Synaptic Inputs and Reduces Excitatory Synaptic Inputs to OFF- and ON-Type Retinal Ganglion Cells in a Chronic Glaucoma Rat Model - Zhou, Xujiao; Li, Gang; Yang, Boqi; Wu, Jihong (Frontiers in Neuroscience, 2019)
Background: Glaucoma is a neurodegenerative disease caused by excitotoxic injury of retinal ganglion cells (RGCs). It has been proved that an important natural dietary flavonoid compound (quercetin) can improve RGC function in our previous high intraocular pressure model prepared by magnetic bead injection into anterior chamber. However, it is unclear whether quercetin can improve the function of RGCs and how quercetin regulates synaptic transmission in chronic glaucoma rat models. Methods: Rat model of chronic glaucoma was prepared by electrocoagulation of superior scleral vein. Electrophysiological electroretinogram was used to detect the photopic negative response (PhNR). Whole-cell patch clamp was used to clamp ON- and OFF-type RGC in normal and 4 weeks retinal sections of glaucoma. Results: Quercetin can restore the decrease of PhNR amplitude caused by chronic glaucoma. The basic miniature GABAergic inhibitory postsynaptic currents (mIPSCs) in RGCs frequency of glaucomatous retinal slices was lower than that of the control group. The frequencies of miniature excitatory postsynaptic currents (mEPSCs) were not significantly different between control and glaucomatous RGCs. The baseline frequencies of GABAergic mIPSCs and mEPSCs in OFF-type glaucomatous RGCs were greater than those in ON-type glaucomatous RGCs. Quercetin increased miniature GABAergic inhibitory neurotransmission to RGCs and decreased miniature glutamatergic excitatory neurotransmission, reduced the excitability of the RGC itself, thus alleviating the excitability of RGCs in glaucomatous slices. Conclusions: Quercetin may be a promising therapeutic agent for improving RGC survival and function in glaucomatous neurodegeneration. Quercetin exerted direct protective effects on RGCs by increasing inhibitory neurotransmission and decreasing excitatory neurotransmission to RGCs, thus reducing excitotoxic damage to those cells in glaucoma.